A general vibration analysis of functionally graded porous structure elements of revolution with general elastic restraints. (1st February 2019) - Guan, Xianlei; Sok, Kyongjin; Wang, Ailun; Shuai, Cijun; Tang, Jinyuan; Wang, Qingshan
Abstract: In this paper, a general vibration analysis of functionally graded porous (FGP) structure elements of revolution with general elastic restraints is performed for the first time. Under the basic framework of the first order shear theory, the moderately thick and thin FGP structure elements of revolution are considered. The specific FGP structure elements include the cylindrical shell, conical shell, spherical shell, cylindrical panel, conical panel and spherical panel. In order to simulate general elastic restraints, the artificial spring boundary technique is adopted this paper. And the modified series solution composed of a standard cosine Fourier series and two auxiliary terms is introduced in the Rayleigh-Ritz method to express the admissible function. A series of numerical examples are conducted, which show that the current model has superior convergence characteristics, computational accuracy and stability. On this basis, a series of innovative results are also given in the paper, which may provide basic data for other algorithm research in the future.